2013
DOI: 10.1007/s13205-013-0130-8
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular synthesis of silver nanoparticles by the Bacillus strain CS 11 isolated from industrialized area

Abstract: Biological synthesis of silver nanoparticles using microorganisms has received profound interest because of their potential to synthesize nanoparticles of various size, shape and morphology. In the current study, synthesis of silver nanoparticles by a bacterial strain (CS 11) isolated from heavy metal contaminated soil is reported. Molecular identification of the isolate showed it as a strain of Bacillus sp. On treating the bacteria with 1 mM AgNO3, it was found to have the ability to form silver nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
143
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(149 citation statements)
references
References 24 publications
6
143
0
Order By: Relevance
“…Therefore Shaverdi et al were able to create AgNPs in 5 minutes, without the need for a cell lysis step by the use of culture supernatant. This extracellular type of formation is a more desirable not only because of the simplicity of purification but also due to the observed increased production rate [33].…”
Section: Nanoparticle Synthesis By Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore Shaverdi et al were able to create AgNPs in 5 minutes, without the need for a cell lysis step by the use of culture supernatant. This extracellular type of formation is a more desirable not only because of the simplicity of purification but also due to the observed increased production rate [33].…”
Section: Nanoparticle Synthesis By Bacteriamentioning
confidence: 99%
“…Although extracellular formation has its advantages, such as lowercost, simpler downstream processing [33], intracellular formation can also be of great importance. In the case of bioremediation, heavy metals such as Cu and Pt need to be removed from contaminated environments.…”
Section: Nanoparticle Synthesis By Fungimentioning
confidence: 99%
“…It is now established that the plants and plant materials act as excellent reducing agents that catalyze bulk materials into nano form.Biological methods of nanoparticles production are regarded as safe, cost-effective, sustainable and environment friendly. Several biological systems including bacteria, fungi, algae and plants have been used in the synthesis of AgNPs [ 5,6,7,8 ].Nanoparticles produced by these methods have protective bio-capping around them, rendering the particles to be stable with no aggregation [ 9 ]. Synthesis of inorganic nanoparticles by biological systems makes nanoparticles more biocompatible and environmentally benign [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, reports have suggested that the extracellular enzyme secreted by microorganism in the culture supernatant is responsible for the reduction of silver ions to silver nanoparticles. 25,26 The study based on extracellular synthesis of silver nanoparticles by Bacillus licheniformis showed that the nitrate reductase enzyme extracellularly secreted by the bacteria in the medium was responsible for the synthesis of silver nanoparticles. 8 For the characterization of the silver nanoparticles, the reaction mixture was monitored by using UV-Vis spectrophotometer for spectral analysis.…”
mentioning
confidence: 99%